2015
DOI: 10.1259/bjr.20150385
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-modulated extended-field chemoradiation plus simultaneous integrated boost in the pre-operative treatment of locally advanced cervical cancer: a dose-escalation study

Abstract: A Phase I radiotherapy dose-escalation trial with SIB-IMRT technique is proposed in cervical cancer. This complex technique is feasible and safe at the recommended doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…This technique has been successfully implemented to treat cancers of various regions such as head and neck, prostate, cervix, etc. [ 6 9 ]. Many studies on SIB has been done for EC in terms of dosimetry [ 10 12 ], proving that it can increase the dose in high-risk areas without increasing the irradiation of normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been successfully implemented to treat cancers of various regions such as head and neck, prostate, cervix, etc. [ 6 9 ]. Many studies on SIB has been done for EC in terms of dosimetry [ 10 12 ], proving that it can increase the dose in high-risk areas without increasing the irradiation of normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The use of IMRT with SIB has greatly improved the quality of dose distribution, reducing treatment duration and allowing higher doses to reach target volumes in cervical cancer. 1416…”
Section: Discussionmentioning
confidence: 99%
“…The recent introduction of intensity-modulated radiation therapy (IMRT) and its dynamic-volumetric applications with simultaneous integrated boost (SIB) allow delivery of different dose levels, achieving dose escalation to the target volumes and optimizing organs at risk (OARs), sparing overall treatment time, with possible applications for cervical cancer treatment. 1416…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 22 Other researchers suggested that the radical surgery should be performed within 6–8 weeks. 9 , 18 , 23 It seems that all the above recommendations are reasonable since the incidence of surgery-associated side effects was relatively low or the consequences were not severe. However, these recommendations rely largely on physician’s experiences rather than research findings.…”
Section: Discussionmentioning
confidence: 99%